Prophylactic Administration of Nanocurcumin Abates the Incidence of Liver Toxicity Induced by an Overdose of Copper Sulfate: Role of CYP4502E1, NF-κB and Bax Expressions - Ahlam Alhusaini; Iman H. Hasan; Nouf Aldowsari; Njood Alsaadan (SAGE Publishing, 2018)
Background: The consequences of excess copper in human tissue are the alterations in the oxidative stress markers and peroxidative damage of membrane lipids. Unselective copper binding may be the clue to damaging impact to protein construction and hence modifying their biological functions. The aim of this study is to match the hepatoprotective efficacy of curcumin (CM) or nanocurcumin (NCM) with that of desferrioxamine (DSF; standard heavy metal chelator) against toxic doses of copper sulphate (CuSO 4 ). Method: All treatments were given simultaneously with CuSO 4 for 7 days. Result: CuSO 4 administration elevated serum alanine transaminase, and hepatic nitric oxide (NO), lipid peroxide, and caspase-3 as well as protein expression of cytochrome P4502E1, and nuclear factor-κB (NF-κB) and Bax gene expressions. On the other hand, hepatic levels of reduced glutathione, superoxide dismutase, and interleukin-10 were decreased, whereas DNA degradation was increased as well compared with the control group. The administration of the aforementioned antioxidants ameliorated all the previous altered measured parameters. Interestingly, NCM achieved the most pronounced hepatoprotective effect nearly equivalent to that of DSF. Conclusion: It was concluded that NCM is considered a promising candidate against CuSO 4 toxicity, and cytochrome P450, NF-κB, and Bax are involved in its toxicity and treatment.